Peningkatan Daya Saing Dan Analisis Kelayakan Usahaternak Domba Pada Perkebunan Kelapa Sawit di Kabupaten Asahan - Rahman, Abdul; Sembiring, Sarim (Universitas Medan Area, 2013)
The Development of Sheep in palm oil plantations in Asahan Regency has a promising future and comparative advantage with DRCR > 1 ( Domestic Resources Cost Ratio ) as the standard of competitiveness. The potential supported by the available forage on palm plantations shows the ideal reproductive potential with litter size of 1.56 . From feasibility analysis there are NPVpositif, B / C ratio is 1.8 and 21 % of IRR > discount rate (12% ).The result indicated that feasible to develop . To increase competitiveness can be done by keeping production and population (1) and the quality standards of at least 25 kg live weight(2) and also continuity of the availability of effort to keep the sheeps throughout the year (3) . To increase competitiveness by exploring local resources to provide additional development and theory of competitiveness, according to sheep farm development oriented agribusiness is sufficient for domestic demand and also to prepare for export market standards. Keyword : Competitiveness, Livestock Sheep